2018
DOI: 10.1007/s10726-018-9577-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining Group Facilitation In Situ: The Use of Formulations in Facilitation Practice

Abstract: In this paper we examine how the talk of the facilitator shapes group workshop interactions by using the conversational object 'formulation'. The data consist of video recordings of a corpus of four facilitated workshops held with management and development teams. By adopting an exploratory video-based investigation using conversational analysis to examine our data, we highlight the significance of three distinct set of formulations used by facilitators in workshops. Specifically, our findings show how formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 49 publications
1
45
0
Order By: Relevance
“…In this facilitated mode, the risk analyst acts as both a modeler and as a facilitator to the risk group (Franco & Montibeller, 2010). Although the quality of the model content will be contingent on the analyst's skillful application of his/her chosen risk modelling method, effective management of the group process will depend on the analyst's facilitation skills (see Franco and Montibeller (2010); Franco and Nielsen (2018); Phillips and Phillips (1993)). The risk analyst should identify the stages of the modeling process that would mostly benefit from using this modeling approach.…”
Section: Design Choices For Managing and Prioritizing Threatsmentioning
confidence: 99%
“…In this facilitated mode, the risk analyst acts as both a modeler and as a facilitator to the risk group (Franco & Montibeller, 2010). Although the quality of the model content will be contingent on the analyst's skillful application of his/her chosen risk modelling method, effective management of the group process will depend on the analyst's facilitation skills (see Franco and Montibeller (2010); Franco and Nielsen (2018); Phillips and Phillips (1993)). The risk analyst should identify the stages of the modeling process that would mostly benefit from using this modeling approach.…”
Section: Design Choices For Managing and Prioritizing Threatsmentioning
confidence: 99%
“…To demonstrate the utility of Conversation Analysis in informing and illuminating facilitation practices, we will explore one study in detail, as a case example, and provide illustrative extracts 1 . The study, by Franco and Neilsen [ 34 ], used Conversation Analysis to examine how facilitator communication shaped work group interactions (across university, business, and local government contexts). The authors found that by using three distinct types of conversational ‘formulations’ (i.e.…”
Section: Objectivementioning
confidence: 99%
“…Although ‘formulations’ are the focus of Franco and Neilson’s [ 34 ] analysis, these are just one of many interactional ‘tools’ or resources facilitators and recipients might use in the facilitation process. We turn now to a summary of additional examples from the Conversation Analysis literature of the interactional resources used to ‘do facilitation’ in interaction.…”
Section: Objectivementioning
confidence: 99%
“…Mingers and Rosenhead 2004;Franco and Montibeller 2010;Franco and Rouwette 2011;Herrera et al 2016;Rouwette 2011;Tavella and Franco 2015). The practice of facilitated workshop to approach group dynamics' difficulties and limits is well-established and used (Franco and Nielsen 2018), to help group engaging in productive discussions and enabling a change in perspectives (Phillips and Phillips 1993).…”
Section: Introductionmentioning
confidence: 99%